Il plurilinguismo letterario siciliano: tecnica e strategia pedagogica nella classe avanzata di italiano LS - Fernández, José García (Sperimentare ed esprimere l’Italianità: Aspetti linguistici e glottodidattici, 2021)
The contemporary Italian literary scene highlights the diverse regional Italian identities. Positive proof of this is the way in which Italian writers describe their region of origin, often referred to in their works through the use of linguistic word plays, grammatical structures or dialectal vocabulary. Sicily, for example, has been an inspiration to many insular writers, intelectuals of the stature of Giuseppina Torregrossa (1956-). Based on her debut novel, L’Assaggiatrice (2007), the didactic proposal presented in this essay employs the literary text as a fundamental pedagogical instrument in the teaching of Italian as a foreign language, in which an attempt is made to foreground the Italian dialectal expressions so as to try to understand the multifaceted Italian territory, trying to make known one of the most recent works of contemporary Italian literature. With both the cultural and the linguistic perspectives in mind, and fully aware of the most recent bibliographical sources about the main theories and techniques in relation to the teaching of Italian, the analysis of the Sicilian terms and dialectal fragments used by Torregrossa in her first novel will allow advanced students of Italian language (levels C1-C2 of the CEFR) to identify different linguistic registers of the national language, going deeply into a subject which is scarcely dealt with in the linguistic syllabi of Italian as a foreign language: dialectal Italianity.